Is a Minimum Age of Juvenile Court Jurisdiction a Necessary Protection? A Case Study in the State of California. (December 2019) - Abrams, Laura S.; Barnert, Elizabeth S.; Mizel, Matthew L.; Bryan, Isaac; Lim, Lynn; Bedros, Antoinette; Soung, Patricia; Harris, Michael
Several U.S. states are considering setting or raising a minimum age of juvenile court jurisdiction. However, there is scant evidence to suggest if a state minimum age law would protect children from developmentally inappropriate proceedings beyond existing capacity and competency statutes. To address this central question, this case study focuses on the state of California and considers (a) existing state laws, (b) state juvenile crime data, and (c) opinions of diverse juvenile justice stakeholders. Triangulated analysis found that a low number of California children below the age of 12 years are petitioned in juvenile court and most are referred for misdemeanor or status offenses. Existing legal protections are present yet inconsistently implemented. A minimum age law would address some of these policy gaps.